Reforming the models of competition law and addressing intersectional discrimination in South Africa - Ndamase, Yolani (Department of Commercial Law, 2025)
The Competition Act of 1998 was enacted as a transformative measure to address our egregious history. This is evident in the inclusion of public interest objectives that sought to promote competition and economic change, particularly for the benefit of businesses owned and controlled by those previously marginalised. As a result, the 1998 Act departs from the mainstream of the Chicago and post-Chicago schools, which had achieved hegemonic status in competition/antitrust law when the Act was passed in 1998. The law diverged significantly from these schools due to general concerns about the concentration of the South African economy in the hands of a few whites and the barriers erected by apartheid that prevented the majority of the population from fairly participating in the economy on racial and gender grounds. Notwithstanding the ambitious goals of the 1998 Act and the expanded goals of the 2018 Amendment Act, the goal of reducing market concentration and increasing the participation of black South Africans has not been adequately addressed. This is partly due to the continued adherence to the general norm of consumer protection. Although one of the main goals of the Act is to promote more excellent ownership dispersion and to increase the ownership shares of historically disadvantaged persons, it continues to treat the category of historically disadvantaged persons without recourse to the nuances and consequences of intersectionality. Therefore, there is a need to explore the possibilities of transformative competition policy which considers intersectionality.